Empowering Electronics Learning through a Hands-on Approach: Arduino Projects in the Classroom - Moncayo, Hugo (2023)
This study addresses the practical approach of Project Based Learning with Arduino in the subject of electronics, the problem identified lies in the disconnection between theory and practical application, which can result in a superficial understanding of the concepts. The objective was to implement projects with Arduino in the classroom and evaluate their impact on the learning of electronics. Mixed methodology was employed to collect qualitative and quantitative data, combining classroom observation, student surveys, and student performance evaluations. The results of the study showed that the hands-on approach with Arduino projects significantly motivated students, increased their interest in the subject, and improved their understanding of electronics concepts. The projects fostered creativity, collaboration, and the development of relevant technical skills. In conclusion, Project Based Learning with Arduino in the electronics subject is revealed as an effective strategy to enhance learning. The results indicate that this hands-on approach can bring students closer to the reality of electronics, preparing them more effectively to face challenges in the professional environment and promoting more meaningful and lasting learning.